2007
DOI: 10.1144/sp282.4
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous motion of Flemish Cap with respect to North America: implications on the formation of Orphan Basin and SE Flemish Cap–Galicia Bank conjugate margins

Abstract: Bouguer gravity anomalies together with deep seismic reflection and magnetic data on both sides of the North Atlantic are used to locate the hinge zones of the Flemish Cap and Galicia Bank within the Iberian and North American plates, regions across which there were abrupt changes in lithospheric extension. The characteristic shape and alignment of these hinge zones suggest that they were conjugate features generated during chrons M25-M0 (Late Jurassic-Early Aptian) around a distally located Euler pole of rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 36 publications
8
88
1
Order By: Relevance
“…Bathymetric contours are in metres. The locations and lateral extents of the major sedimentary basins are shown in tan colour (Enachescu et al 2004c;Sibuet et al 2007b;Naylor & Shannon 2011). Superimposed structural components on the Newfoundland margin were adapted from the structural map presented by Sibuet et al (2007b) and originally modified from Enachescu et al (2004a,b,c several broad trends can be observed in the depth to basement map across the conjugate margins (Fig.…”
Section: Inversion Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bathymetric contours are in metres. The locations and lateral extents of the major sedimentary basins are shown in tan colour (Enachescu et al 2004c;Sibuet et al 2007b;Naylor & Shannon 2011). Superimposed structural components on the Newfoundland margin were adapted from the structural map presented by Sibuet et al (2007b) and originally modified from Enachescu et al (2004a,b,c several broad trends can be observed in the depth to basement map across the conjugate margins (Fig.…”
Section: Inversion Resultsmentioning
confidence: 99%
“…There is also seismic evidence that rifting occurred in the Rockall Basin as early as the Permo-Triassic (Shannon et al 1999;Štolfová & Shannon 2009;Tyrrell et al 2010;Naylor & Shannon 2011). However, the Flemish Cap was not affected until the Early Jurassic (Sibuet et al 2007b).…”
Section: Tectonic Settingmentioning
confidence: 95%
See 3 more Smart Citations